A STUDY OF THE PHYSICO-MECHANICAL PROPERTIES IN SHORT BLEACHING SEQUENCES - Almeida Ferraz, Ana Paula [UNESP]; Ventorim, Gustavo [UNESP] (Univ Federal Vicosa, 2018)
The kraft pulp of Eucalyptus spp. is relatively easy to be bleached. Therefore, studies have been carried out to reduce the number of stages of bleaching in the plant and minimize process costs. The present work aimed to evaluate the use of two short bleaching sequences in the physico-mechanical properties of cellulosic pulp as well as to compare these values to the ones obtained by usual bleaching sequences. The four bleaching sequences were ECF (elemental chlorine free), D-0(E+P)D1P, A(HT)D(0)(E+P)D1P, and A(HT)DP and A(HT)D (PO). For each bleaching sequence the brightness, brightness reversion and total cost of reagents were evaluated. Physical and mechanical analyses were performed according to the methodologies of the Technical Association of the Pulp and Paper Industry (TAPPI, 2002). The A(HT)D (PO) sequence showed higher brightness, less brightness reversion, lower total cost and better smoothness compared to the reference sequences. However, it had a lower tear index and a lower compression index. The A(HT)DP sequence did not reach target brightness, however, it presented brightness reversion and lower total cost than the reference sequences. The A(HT)DP sequences showed high compression and smoothness, but presented a low compression index.
Keywords: Cellulose; Eucalyptus; Short sequences; Elemental chlorine free bleaching